Bispecific NK-cell engager targeting BCMA elicits stronger antitumor effects and produces less proinflammatory cytokines than T-cell engager - Xiao, Xinghui; Cheng, Ying; Zheng, Xiaodong; Fang, Yuhang; Zhang, Yu; Sun, Rui; Tian, Zhigang; Sun, Haoyu (Frontiers in Immunology, 2023)
Bispecific antibodies have attracted more attention in recent years for the treatment of tumors, in which most of them target CD3, which mediates the killing of tumor cells by T cells. However, T-cell engager may cause serious side effects, including neurotoxicity and cytokine release syndrome. More safe treatments are still needed to address the unmet medical needs, and NK-cell-based immunotherapy is a safer and effective way to treat tumors. Our study developed two IgG-like bispecific antibodies with the same configuration: BT1 (BCMA×CD3) attracted T cells and tumor cells, while BK1 (BCMA×CD16) attracted NK cells and tumor cells. Our study showed that BK1 mediated NK-cell activation and upregulated the expression of CD69, CD107a, IFN-γ and TNF. In addition, BK1 elicited a stronger antitumor effect than BT1 both in vitro and in vivo. Combinatorial treatment (BK1+BT1) showed a stronger antitumor effect than either treatment alone, as indicated by in vitro experiments and in vivo murine models. More importantly, BK1 induced fewer proinflammatory cytokines than BT1 both in vitro and in vivo. Surprisingly, BK1 reduced cytokine production in the combinatorial treatment, suggesting the indispensable role of NK cells in the control of cytokine secretion by T cells. In conclusion, our study compared NK-cell engagers and T-cell engagers both targeting BCMA. The results indicated that NK-cell engagers were more effective with fewer proinflammatory cytokine production. Furthermore, the use of NK-cell engagers in combinatorial treatment helped to reduce cytokine secretion by T cells, suggesting a bright future for NK-cell engagers in clinical settings.